2012
DOI: 10.1038/ejhg.2012.169
|View full text |Cite
|
Sign up to set email alerts
|

Maternal ABCA1 genotype is associated with severity of Smith–Lemli–Opitz syndrome and with viability of patients homozygous for null mutations

Abstract: The Smith-Lemli-Opitz syndrome (SLOS [MIM 270400]) is an autosomal recessive malformation syndrome that shows a great variability with regard to severity. SLOS is caused by mutations in the D7sterol-reductase gene (DHCR7), which disrupt cholesterol biosynthesis. Phenotypic variability of the disease is already known to be associated with maternal apolipoprotein E (ApoE) genotype. The aim of this study was to detect additional modifiers of the SLOS phenotype. We examined the association of SLOS severity with va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…ABCA1 has also been recently identified as a gene whose variants in the mother significantly correlated with the severity of SLOS phenotype of the infant. This observation suggested that placental cholesterol transfer pathways are not only vital for fetal development but also present as a plausible target for prenatal SLOS therapy [36]. Furthermore, maternally derived cholesterol plays a role in the growth and the development of fetuses unaffected with SLOS.…”
Section: Importance Of Cholesterolmentioning
confidence: 99%
“…ABCA1 has also been recently identified as a gene whose variants in the mother significantly correlated with the severity of SLOS phenotype of the infant. This observation suggested that placental cholesterol transfer pathways are not only vital for fetal development but also present as a plausible target for prenatal SLOS therapy [36]. Furthermore, maternally derived cholesterol plays a role in the growth and the development of fetuses unaffected with SLOS.…”
Section: Importance Of Cholesterolmentioning
confidence: 99%
“…Recently, Lanthaler and colleagues [52] also discovered that specific maternal ABCA1 genotypes are associated with the severity of SLOS in offspring. From these studies we can conclude that disturbances in maternal cholesterol levels are associated with adverse pregnancy outcomes.…”
Section: Low Maternal Cholesterol and Adverse Pregnancy Outcomesmentioning
confidence: 99%
“…The correlation of maternal ApoE genotype with disease severity persisted after stratification for DHCR7 genotype. Furthermore, Lanthaler, Steichen-Gersdorf, Kollerits, Zschocke, and Witsch-Baumgartner (2013) reported that maternal ABCA1 genotype is an additional genetic modifier in SLOS. The p.Arg1587Lys polymorphism in maternal A BCA1 gene was associated with milder clinical phenotypes.…”
Section: | Discussionmentioning
confidence: 99%